FUNCTIONAL CAPACITY EVALUATION IN ELDERLY: INTEGRATIVE REVIEW (Fiep Bulletin - online, 2014)
This research consists of an integrative literature review, aimed at investigating the scientific production related to elderly functional capacity. The BDENF, LILACS, and SciELO databases were consulted during the sample period, which was from January 2001 to September 2011. Most of the eleven scientific productions analyzed were quantitative researches, focusing on elderly multidimensionality. The small number of articles reveals a gap in knowledge production of nursing in this subject, and also the need for new research capable of pointing out new elderly care strategies and, consequently, quality of life improvement for this population group.
Keywords: Functional Capacity; Elderly Health; Nursing.